Design of a man-wearable control station for a robotic rescue system - Fong, Wai K (Department of Mechanical Engineering, 2017)
This report details the design, development, and testing of a man-wearable operator control station for the use of a low-cost robotic system in Urban Search and Rescue (USAR). The complete system, dubbed the "Scarab", is the 1st generation developed and built in the Robotics and Agents Research Laboratory (RARL) at the University of Cape Town (UCT), and was a joint effort between three MSc students. Robots have found a place in USAR as replaceable units which can be deployed into dangerous and confined voids in the place of humans. As such, they have been utilized in a large variety of disaster environments including ground, aerial, and underwater scenarios, and have been gathering research momentum since their first documented deployment in the rescue operations surrounding the 9/11 terrorist attacks. However one issue is their cost as they are not economical solutions, making them less viable for inclusion into a rescue mission as well as negatively affecting the operator‟s decisions in order to prioritise the safety of the unit. Another concern is their difficulty of transport, which becomes dependent on the size and portability of the robot. As such, the Scarab system was conceived to provide a deployable robotic platform which was lowcost, with a budget goal of US $ 500. To address the transportability concerns, it aimed to be portable and light-weight; being able to be thrown through a window by a single hand and withstanding a drop height of 3 m. It includes an internal sensor payload which incorporates an array of sensors and electronics, including temperature monitors and two cameras to provide both a normal and IR video feed. Two LED spotlights are used for navigation, and a microphone and buzzer is included for interaction with any discovered survivors. The operator station acts as the user interface between the operator and the robotic platform. It aimed to be as intuitive as possible, providing quick deployment and minimalizing the training time required for its operation. To further enhance the Scarab system‟s portability, it was designed to be a manwearable system, allowing the operator to carry the robotic platform on their back. It also acts as a charging station, supplying power to the robotic platform‟s on-board charging circuitry. The control station‟s mechanical chassis serves as the man-wearable component of the system, with the functionality being achieved by integration onto a tactical vest. This allows the operator to take the complete system on and off as a single unit without assistance, and uses two mounting brackets to dock the robotic platform. Key areas focussed upon during design were the weight and accessibility of the system, as well as providing a rugged housing for the internal electronics. All parts were manufactured in the UCT Mechanical Engineering workshop.